Green Supply Chain Management practices and impact on firm performance: The moderating effect of collaborative capability. (November 2021) - Samad, Sarminah; Nilashi, Mehrbakhsh; Almulihi, Ahmed; Alrizq, Mesfer; Alghamdi, Abdullah; Mohd, Saidatulakmal; Ahmadi, Hossein; Syed Azhar, Sharifah Nurlaili Farhana
Abstract: The environmental effects of supply chain operations are under the significant influence of Green Supply Chain Management (GSCM), with a potential enhancement of organizational sustainability performance. Even though previous studies have pointed to the contribution of integration of various activities associated with GSCM, no investigations have been carried out for the possible interdependencies of these activities and their application effects. Consequently, this paper aims at investigating the associations of GSCM methods and performance of manufacturing firms using the Natural Resource-Based View (NRBV) as well as Institutional Theory. The collected data from manufacturing firms were analyzed using the partial least squares technique. Accordingly, mimetic, normative, and coercive pressures were found to affect GSCM positively and significantly. Moreover, the GSCM and the firms' environmental, operational and economic performances were found to be positively and significantly associated. In addition, according to the moderation analysis, collaborative capabilities had significant moderating effects on the association of green chain management and environmental as well as economic performance. However, collaborative capabilities could not moderate the association of GSCM and operational performance. Managers, supply chain specialists and also policy makers would benefit from the findings of the present study along with the inspirations resulting from the contribution of specific drivers in implementing GSCM methods, while application of the mentioned methods could be effective in achieving the desired performance levels. Furthermore, industrial sectors are provided with managerial and theoretical insights by the results obtained in the present paper to concentrate on environmental awareness through the adoption of GSCM methods. Highlights: Green supply chain management practices and impact on firm performance. The use of Natural Resource-Based View (NRBV). 270 manufacturing firms in Malaysia from a variety of sectors were studied.